A simple and efficient parameter extraction procedure for physics based IGBT models - Rui Filipe Marques Chibante (2004)
Extraction of parameters for models of power semiconductors is a need for researchers working with development of power circuits. One of the drawbacks of physics based models is how to extract the numerous parameters to describe the model. Different approaches have been taken, most of them cumbersome to be solved. This paper presents a simple and accurate method of parameter extraction for physics based IGBT models. The procedure, based on an optimization algorithm (simulated annealing), is easy to implement and is efficient for extraction of a large number of parameters needed for physics based IGBT models, only requiring some experimental points of DC and resistive load characteristics. It is validated by comparing experimental and simulated results, at various operating conditions, using a Finite Element, physics based, IGBT model.